MODEL PENGEMBANGAN PERTANIAN CENGKEH BERBASIS KEARIFAN LOKAL: STUDI KASUS DI DESA TALLUNGURA, KECAMATAN CURIO, KABUPATEN ENREKANG - Najib, Muh.; Irmayani, Irmayani; Darmawan, Darmawan (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to identify and analyze the development model of local wisdom-based clove farming in Tallungura Village, Curio Sub-district, Enrekang Regency. The research location was purposively selected due to the existence of local wisdom that is still strong and the large area of clove farming. The research was conducted in August 2023 involving all members of the Sauduran Farmer Group (30 farmers) as samples using the census method. Data were collected through structured interviews, analyzed descriptively using the 5W 1H method (What, Why, Who, When, Where, How) to identify and understand the practice of local wisdom applied in clove cultivation. The results showed that the local wisdom applied includes the selection of superior seeds, the use of natural fertilizers, traditional herbs for pest control, planting protective trees, traditional rituals, and mutual cooperation. This wisdom is maintained because it is considered effective in improving the quality of crop yields, preserving the environment, preserving traditions, and strengthening social solidarity. Its application involves individual farmers, farmer groups and the village community at large, carried out throughout the year as needed in fields, gardens and village meeting areas. This study concluded that the local wisdom-based clove farming development model in Tallungura Village has great potential to support agribusiness sustainability by utilizing local cultural values. Therefore, preserving local wisdom is crucial to maintaining agricultural productivity and social harmony in the community.